A study of potential Load Bearing Masonry (LBM) system in Malaysia construction industry - Ramli, N. A.; Abdullah, Che Sobry; Mohd Nawi, Mohd Nasrun (EDP Sciences, 2014)
To overcome the problems in increasing of material prices, land prices, shortage of skilled workers, equipping low cost housing demands and maintained the cost of the constructing at an affordable price, there is a need to find the alternative solution for constructing method.The use of the load bearing masonry system (LBM) has been identified as a sustainable and an effective alternative method for the construction industry.The system offers several advantages in term of cost and speed of the construction, durability, strength, environmentally friendly practices and aesthetic qualities.Despite these advantages, unfortunately, this system has not been widely used in Malaysia compared to reinforced concrete (RC) frame construction. Therefore, this paper aims to discuss the advantages and potential of the system implementation to Malaysia construction industry in the future.